Challenges and pitfalls when implementing renal replacement therapy in the ICU - Mehta, Ravindra L (Crit Care, 2015)
Several new methods of renal replacement therapy (RRT) are now available for treating patients in the ICU setting. However, utilization of RRT in the ICU is subject to considerable variation and the need for RRT is associated with worse outcomes. Several factors influence the application of dialysis and reflect the interplay of patient and process of care elements that are dynamic in nature. Despite multiple studies evaluating RRT and its application, there are gaps in our knowledge that must be overcome to improve outcomes. This article discusses some of the important issues that require attention in delivering RRT in critically ill patients and provides a framework for the optimal use of RRT in the ICU.